2021
DOI: 10.15766/mep_2374-8265.11119
|View full text |Cite
|
Sign up to set email alerts
|

Disaster Preparedness Training for Emergency Medicine Residents Using a Tabletop Exercise

Abstract: Introduction Emergency medicine (EM) physicians serve at the frontline of disasters in our communities. The 2016 Model of Clinical Practice according to the American Board of EM identifies disaster management as an integral task of EM physicians. We described a low-cost and feasible tabletop exercise to implement such training for EM residents. Methods The exercise took place during 2 hours of resident didactic time. A lecture introduced the incident command system (ICS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 14 publications
1
30
0
1
Order By: Relevance
“…For the quasi-experimental studies, usually none ( k = 4), one question ( k = 23) or two questions ( k = 13) were answered with no . There was only one paper for which four out of nine questions were answered in the negative [ 46 ]. The higher risk of bias in the quasi-experimental studies was mainly based on question 4, which assesses the control group because a large part of the studies had a single group pre-post design ( k = 35).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the quasi-experimental studies, usually none ( k = 4), one question ( k = 23) or two questions ( k = 13) were answered with no . There was only one paper for which four out of nine questions were answered in the negative [ 46 ]. The higher risk of bias in the quasi-experimental studies was mainly based on question 4, which assesses the control group because a large part of the studies had a single group pre-post design ( k = 35).…”
Section: Resultsmentioning
confidence: 99%
“…All other studies measured individual performance only. Furthermore, several studies used self-reported measures, including preparedness/readiness [39,[41][42][43][44] and (self-)confidence [45][46][47][48][49][50].…”
Section: Research Question 2: Effectiveness Indicatorsmentioning
confidence: 99%
“…Unlike lectures, disaster exercises may be a good method to help learners gain knowledge or skills. Tabletop exercises have been used to teach ICS effectively and at a low cost (Sena et al, 2021); however, learners may not feel the reality of the disaster or lack engagement in the disaster response in this type of exercise (Knight et al, 2010). By contrast, full-scale exercises can create an environment close to disaster but may require considerable funding and a large amount of educational resources (Hu, Liu and Li, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Because disasters do not usually happen frequently, many learners may lose their skills or knowledge due to a lack of exposure or practice (Sena et al, 2021). Therefore, disaster training should be repeated at regular intervals to prepare responders for unexpected events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation